Economics of futures trading, for commercial and personal profit - Hieronymus, Thomas Applegate (New York, Commodity Research Bureau, 1971)
Futures trading is a remarkably close approximation to the classical economic concept of pure competition.
Includes index
Includes bibliographical references.
II 16/01/2019
Loans
Keywords: Futures; Commodity exchanges; Speculation